Quality of Health Services at the Tamalanrea Community Health Center Makassar City - Sakawati, Herlina; Nikmawati, Andi; Halim, Didin (Jurnal Aktor, 2024)
Quality of Health Services at the Tamalanrea Community Health Center Makassar City. Thesis, State Administration Study Program, Department of State Administration Sciences, Faculty of Social Sciences and Law, Makassar State University, supervised by Mrs. Herlina Sakawati and Mr. Didin.This study aims to determine the Quality of Health Services at the Tamalanrea Community Health Center in Makassar City. This type of research is qualitative and produces descriptive data. With data collection techniques carried out by observation, interviews, documentation. The data analysis techniques used consist of data reduction, data presentation and conclusions.The results showed that the quality of service at Puskesmas Tamalanrea showed that the comprehensive dimension was not fully in accordance with the expectations of the community in providing services at Puskesmas Tamalanrea. The quality of Puskesmas services that are considered not in accordance with community expectations can be seen in the tanggible dimension (physical appearance) facilities such as waiting rooms and toilets still need improvement so that patients feel uncomfortable with the situation. In addition, the reliability dimension (ability) shows the length of the registration process at the counter makes patients complain because the medical record data filling system still uses the system. The quality of health services that are considered to be in accordance with community expectations is in the dimension of assurance, where the health apparatus has fully provided good and quality service, and empathy where the health apparatus provides personal treatment or attention to the community served, so as to create an atmosphere of harmony and mutual understanding between those who serve and those served.